Produtos vegetais análogos de cárneos e pescado comercializados no Brasil: caracterização a partir de informações da rotulagem. - Marina de Paula Penna e Palhares (2023)
Plant-based meat analogues regulation is under debate in Brazil, thus understand the characteristics of products available on the market is essential for design standards that will effectively fill the existing regulatory gap. The objective was, therefore, to evaluate plant-based meat and fish analogues in terms of official designation and other names; claims; ingredients, allergen alerts; and nutritional composition. 111 labels were collected, from 24 brands and sixteen categories. Hamburger analogues stood out (43.2%). Terms referring to animal products were observed in 77.5% of official designation and 95.7% of other names. Only one label (0.9%) did not have animal products terms. Terms related to plant origin appeared in 52.3% of official designation and 58.6% of other names. Absence of animal products was declared in 4.3% of other names. Altogether, in 64.0% of labels it was pointed out plant origin or absence of animal products. Ingredients specification was observed in 61.3% of the official designation and 14.3% of other names, 62.2% of total labels. Claims about plant origin and absence of animal products were observed in 91.9% of labels, claims of similarity with meat or fish products in 27.9%, environmental sustainability or animal protection claims in 38.7% and healthiness or naturalness claims in 47.7%. Nutritional claims were observed in 57.7% of labels, with protein claims being the main type. 68.4% of the products had between six and 15 ingredients. 77.5% had additives, with six being the maximum amount. Ten technological functions of additives were identified, with flavoring being the most frequent. The presence of protein products was found in 79.3% of products, with soy protein being the most frequent. Oils or fats were observed in 79.3% of products, with sunflower oil being the main one. Allergenic alerts were found in 74.2% of labels and preventive alerts in 30.3%. Comparing nutritional parameters between categories with three or more samples, significant differences were identified for carbohydrates only. When the nutritional parameters of plant-based meat analogues were compared with those of animal products from the same categories, significant differences were observed. Results found demonstrate nonconformities and lack of standardization in labeling information. Although they are ultra-processed products, a considerable part of meat and fish analogues is positioned in the market as a healthy option. Such inconsistencies must be considerate in the regulatory process.